2014
DOI: 10.4062/biomolther.2014.058
|View full text |Cite
|
Sign up to set email alerts
|

Strain Differences in the Chronic Mild Stress Animal Model of Depression and Anxiety in Mice

Abstract: Chronic mild stress (CMS) has been reported to induce an anhedonic-like state in mice that resembles some of the symptoms of human depression. In the present study, we used a chronic mild stress animal model of depression and anxiety to examine the responses of two strains of mice that have different behavioral responsiveness. An outbred ICR and an inbred C57BL/6 strain of mice were selected because they are widely used strains in behavioral tests. The results showed that the inbred C57BL/6 and outbred ICR mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…We observed increased exploratory activity specifically in DBA in four independent tests: in the first light phase of the 24h activity test, in the open field, elevated plus maze as well as in the SPSN test, while BL6 showed hyperactivity in elevated plus maze and a trend in the open field and 24h activity. Similar increases in center time and open arm visits have been reported before [ 46 , 69 ], but other studies reported reductions [ 70 73 ]. We attribute these contradictory results as being caused by differences in housing condition, testing history and strain background, factors that have all been shown to influence exploration in open field and elevated plus maze [ 74 ].…”
Section: Discussionsupporting
confidence: 83%
“…We observed increased exploratory activity specifically in DBA in four independent tests: in the first light phase of the 24h activity test, in the open field, elevated plus maze as well as in the SPSN test, while BL6 showed hyperactivity in elevated plus maze and a trend in the open field and 24h activity. Similar increases in center time and open arm visits have been reported before [ 46 , 69 ], but other studies reported reductions [ 70 73 ]. We attribute these contradictory results as being caused by differences in housing condition, testing history and strain background, factors that have all been shown to influence exploration in open field and elevated plus maze [ 74 ].…”
Section: Discussionsupporting
confidence: 83%
“…Firstly, the rats we used are outbred. Since genetic differences may contribute to the behavioral effects of rodents in models of depression [ 58 ], it would be more ideal to use inbred strains in the future. Secondly, we were unable to have a pre- and post-stress brain comparison due to laboratory regulations limiting the physical movement of the animals after r-fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…The novelty-suppressed feeding test (NSF) was adapted from previous studies 40 , 41 . The mice were deprived of food for 24 h before the test in their home cages.…”
Section: Methodsmentioning
confidence: 99%